2021
DOI: 10.1038/s41536-021-00138-y
|View full text |Cite
|
Sign up to set email alerts
|

Process analysis of pluripotent stem cell differentiation to megakaryocytes to make platelets applying European GMP

Abstract: Quality, traceability and reproducibility are crucial factors in the reliable manufacture of cellular therapeutics, as part of the overall framework of Good Manufacturing Practice (GMP). As more and more cellular therapeutics progress towards the clinic and research protocols are adapted to comply with GMP standards, guidelines for safe and efficient adaptation have become increasingly relevant. In this paper, we describe the process analysis of megakaryocyte manufacture from induced pluripotent stem cells wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Optimizing cell culture conditions to increase cell output and diminish the cost of goods remains one of the major challenges in translating iPSC-derived cellular products to the clinic ( 21 , 53 ). Using the set of MKP markers identified here, we found that adjusting oxygen and cytokine conditions can increase MKP generation, maximizing mature MK generation.…”
Section: Discussionmentioning
confidence: 99%
“…Optimizing cell culture conditions to increase cell output and diminish the cost of goods remains one of the major challenges in translating iPSC-derived cellular products to the clinic ( 21 , 53 ). Using the set of MKP markers identified here, we found that adjusting oxygen and cytokine conditions can increase MKP generation, maximizing mature MK generation.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet numbers in the range of >10 8 , which are currently obtained by many researchers in laboratory scale, will be sufficient to perform well-designed mechanistic studies towards better understanding regenerative platelet functions. Further improvements of hiPSC-derived platelet production technologies will consider GMP requirements [12,25,50] and might focus on using particularly histocompatible hiPSCs [12,14,25,51,52]. This will enable providing clinical platelet units, particularly for patients suffering from alloimmunization against frequent antigens, otherwise lacking suitable donors, in the near future.…”
Section: Discussionmentioning
confidence: 99%
“… 7 He also emphasized that understanding the culture and differentiation process through process analytical tools, with a focus on those stages that were most challenging to develop into a GMP environment, had been key to progress towards a final manufacturing process. 8 Dr Ghevaert outlined the significant work involved in the development of new potency assays including an in vitro thrombus formation and a laser‐induced injury model in NSG mice. 6 , 8 A major issue that the whole hPSC manufacturing field is facing today, is the selection of appropriate manufacturing cell lines.…”
Section: Manufacturing Scale‐up and Differentiationmentioning
confidence: 99%
“… 8 Dr Ghevaert outlined the significant work involved in the development of new potency assays including an in vitro thrombus formation and a laser‐induced injury model in NSG mice. 6 , 8 A major issue that the whole hPSC manufacturing field is facing today, is the selection of appropriate manufacturing cell lines. Dr Ghevaert explained the significant diversity that the UKRMP programme had discovered in the differentiation characteristics of different hESC lines.…”
Section: Manufacturing Scale‐up and Differentiationmentioning
confidence: 99%
See 1 more Smart Citation